Impact of tsetse control on land use in the semi-arid zone of Zimbabwe - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Impact of tsetse control on land use in the semi-arid zone of Zimbabwe by J Pender and J Rosenberg 1995 38pp price UKL 10 00 ISBN 0 85954 430 3